Real-time investigation of the roles of ATP hydrolysis by UvrA and UvrB during DNA damage recognition in nucleotide excision repair - Thanyalak Kraithong (2022)
Nucleotide excision repair (NER) stands out among other DNA repair systems for its ability to process a diverse set of unrelated DNA lesions. In bacteria, NER damage detection is orchestrated by the UvrA and UvrB proteins, which form the UvrA2-UvrB2 (UvrAB) damage sensing complex. The highly versatile damage recognition is accomplished in two ATP-dependent steps. In the first step, the UvrAB complex samples the DNA in search of lesion. Subsequently, the presence of DNA damage is verified within the UvrB-DNA complex after UvrA has dissociated. Although the mechanism of bacterial NER damage detection has been extensively investigated, the role of ATP binding and hydrolysis by UvrA and UvrB during this process remains incompletely understood. Here, we report a pre-steady state kinetics Förster resonance energy transfer (FRET) study of the real-time interaction between UvrA, UvrB, and damaged DNA during lesion detection. By using UvrA and UvrB mutants harboring site-specific mutations in the ATP binding sites, we show for the first time that the dissociation of UvrA from the UvrAB-DNA complex does not require ATP hydrolysis by UvrB. We find that ATP hydrolysis by UvrA is not essential, but somehow facilitates the formation of UvrB-DNA complex, with ATP hydrolysis at the proximal site of UvrA playing a more critical role. Consistent with previous reports, our results indicated that the ATPase activity of UvrB is essential for the formation of UvrB-DNA complex but is not required for the binding of the UvrAB complex to DNA.